2012
DOI: 10.4103/0253-7176.108230
|View full text |Cite
|
Sign up to set email alerts
|

Suicidality and Suicide Attempt in a Young Female on Long-Term Sertraline Treatment

Abstract: A 22-year-old woman who was on sertraline 50 mg oral tablets once daily for 2 years for treatment of major depression took 30 such tablets (1500 mg) in a fit of rage, with a suicidal intent. She presented to the Emergency Department of a Tertiary Care Hospital with tachycardia, tachypnea, hypertension, tremors, agitation, confusion, vomiting, and hyperthermia. The patient was admitted and treated symptomatically, and sertraline therapy was discontinued. The unwanted effects subsided within 48 h and she recover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Similarly, there are some studies that indicated SRT-induced tachycardia. [45][46][47][48][49][50][51] ECG is routinely used in the determination of cardiotoxicity induced by various agents. 1 An ECG is a recording of the heart's electrical activity as a graph consisting of PQRST complexes.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, there are some studies that indicated SRT-induced tachycardia. [45][46][47][48][49][50][51] ECG is routinely used in the determination of cardiotoxicity induced by various agents. 1 An ECG is a recording of the heart's electrical activity as a graph consisting of PQRST complexes.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of sertraline treatment for both disorders may include direct and indirect effects. Vasodilatory, antiplatelet and endothelium- protective effects of sertraline [62] , [63] may contribute to the direct effect. The indirect effect may result from the use of sertraline to treat depression, and recovery from depression might contribute to an amelioration of heart injury.…”
Section: Discussionmentioning
confidence: 99%
“…The accurate mechanism of protective function of sertraline in cardiomyocytes has not been yet clearly known. But, several studies have described that sertraline has vasodilatory role, the antiplatelet effects and protective effects of vascular endothelial cells and with the help of these factors involves in the inhibition of myocardial damage (28,29). Since, in this study we encountered a significant reduction in homocysteine and cTnI in rats in dose of 80 mg, hence, sertraline can play fundamental role in the heart protecting.…”
Section: Pharm Biomed Res 2017; 3(3): 20mentioning
confidence: 55%